Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Perusahaan Bimatex - Rezaka, Kafendar Bela, Jati Waskito, SE, M.Si (2016)
This research aim to know do communications and working environment have influence to employee's performance and to know combination from communications and working environment has influence to employee's performance. Population which used at this research is employee's company of BimaTex that amounted to 80 employees. This research use sample counted 44 respondents; data collecting method used questionnaires with simple random sampling as its intake technique. Examination of hypothesis in this research use statistical model analysis consisting of validity test, reliability test, classiccal assumption test, doubled linear regression, test of F, test of t, and coefficient of determinacy (R2). The result of research show there are relation between independent variable that is communications and working environment to variable of dependent that is employee's performance. Value of hypothesis test (ttest) obtained that communications variable have influence to employee's performance, then working environmental variable have influence to employees performance. Test of F showing that communications and working environment by together have influence to employee's performance. Coefficient of determinacy test of employee's performance influenced by communications variable and working environment and the model have got away from result of classiccal assumption.